Ten Years of External Quality Control for Cellular Therapy Products in France - Panterne, Béatrice; Richard, Marie-Jeanne; Sabatini, Christine; Ardiot, Sophie; Huyghe, Gérard; Lemarié, Claude; Pouthier, Fabienne; Mouillot, Laurence (IntechOpen, 2011)
None